Preparation method of defect-metal-doped titanium oxide nanotube array supercapacitor electrode material

By introducing Nb and Ti3+/oxygen vacancy co-doping into the titanium oxide nanotube array electrode material, the problem of low charge transfer efficiency is solved, and defect-type metal-doped titanium oxide nanoparticles with high specific surface area and high electrochemical performance are achieved. The preparation of tube array supercapacitor electrode materials improves surface capacitance performance and reduces preparation costs.

CN114864290BActive Publication Date: 2025-01-24SHANGHAI INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210128687.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-11
Publication Date
2025-01-24
Estimated Expiration
2042-02-11

AI Technical Summary

Technical Problem

The charge transfer efficiency of the titanium oxide nanotube array electrode material is low, resulting in insufficient surface capacitance, limiting its application in the field of supercapacitors.

Method used

Using Ti-Nb alloy as the anode, nanotube arrays are grown in situ on the alloy substrate through anodization, followed by high-temperature heat treatment and electrochemical reduction, and Nb and Ti3+/oxygen vacancy co-doping are introduced to form defect-type metal doping. Titanium oxide nanotube array.

Benefits of technology

It significantly improves the charge transfer efficiency and specific surface area, improves the electrochemical performance of the electrode material, and makes the surface capacitance reach the level of several mF cm-2, while reducing the preparation cost and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114864290B_ABST
    Figure CN114864290B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a defective-metal-doped titanium oxide nanotube array supercapacitor electrode material, which specifically comprises the following steps: a Ti-Nb alloy sheet after pretreatment and drying is subjected to anodization and heat treatment to crystallize to obtain a crystallized Nb-doped titanium oxide nanotube array, and then a Ti-Nb alloy sheet is subjected to a one-step electrochemical reduction method to obtain a Ti-Nb alloy sheet. 3+ / oxygen vacancies and Nb co-doped titanium oxide nanotube array is a defect-type metal-doped titanium oxide supercapacitor electrode material. The Ti obtained by the present invention 3+ The titanium oxide nanotube array co-doped with oxygen vacancies and Nb as a supercapacitor electrode material has the electrochemical characteristics of high charge transfer efficiency, high specific capacitance and high rate performance, and has the characteristics of non-toxic raw materials, controllable process, convenient and fast, and easy to industrialize production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material technology and new energy, and specifically relates to a method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material. Background Art

[0002] Supercapacitors, also known as electrochemical capacitors, are energy storage devices with both high energy density and high power density. They have the characteristics of fast charge and discharge speed and high cycle stability, and can provide a safe use environment for hybrid vehicles, memory backup systems, energy management systems, and mobile electronic devices. For supercapacitors, excellent electrode materials can greatly improve the energy density and power density of supercapacitors, so the development of advanced electrode materials is the first choice to improve the electrochemical performance of supercapacitors.

[0003] One-dimensional TiO 2 Nanotube arrays are an excellent electrode material with the characteristics of being cheap, non-toxic, chemically stable, and having a high specific surface area. In particular, the in-situ grown nanotube arrays prepared by anodization are closely arranged and vertically oriented, providing more active sites for charge adsorption and good channels for charge transport. However, due to the 2 It is an n-type semiconductor material with large resistance and low charge transfer efficiency, which limits its application in the field of supercapacitors. 2 Intrinsic electrochemical performance, the current TiO 2 The main methods for optimization and modification include anodizing process optimization, heat treatment process optimization, metal body phase doping and Ti 3+ / oxygen vacancy self-doping, etc. The researchers first optimized the anodization and heat treatment processes to prepare TiO with high specific surface area and high charge transfer efficiency. 2 Although the specific surface area of ​​the electrode material can be improved to a certain extent by optimizing the anodizing process, the heat treatment at different temperatures and times only has a negative effect on the surface area of ​​TiO 2 The charge transfer efficiency cannot be significantly improved by adjusting the crystal phase, resulting in the electrochemical performance still being in the range of μF cm -2 grade.

[0004] Metal bulk doping has been shown to improve the electrochemical performance of electrode materials. For example, a large amount of Ni is introduced into titanium sheets to change the TiO 2 Lattice crystallinity, thereby improving the charge transfer efficiency of electrode materials. Mn bulk doping can introduce defects on the surface of electrode materials and improve the conductivity of electrode materials. V 4+ / V 5+ The reversible redox reaction of TiO 2Nanotubes provide pseudocapacitance, thereby improving TiO 2 Intrinsic electrochemical performance. Although the above metal doping has improved the electrochemical performance of titanium oxide nanotube arrays to a certain extent, it relies on the input of a large amount of metal elements, has high preparation costs, and has unsatisfactory performance. In order to improve the charge transfer efficiency of electrode materials, researchers have found that by adding a large amount of metal elements to the TiO 2 Appropriate amount of Ti is introduced into the surface 3+ / Oxygen vacancies can increase the carrier density by 5 orders of magnitude, which is also an effective way to improve the charge transfer efficiency.

[0005] Currently 3+ / Oxygen vacancy doping methods include vacuum heat treatment, H 2 Reduction, H plasma reduction, metal reduction and strong reducing agent reduction. However, the current methods all have problems such as complex preparation process, long time consumption, high equipment investment cost and unstable performance, making it difficult to achieve industrial production. Therefore, research and development of an electrode material with low preparation cost, simple process and stable performance, high charge transfer efficiency and high specific surface area has important theoretical research significance and practical application value. Summary of the invention

[0006] The purpose of the present invention is to address the problems of low charge transfer efficiency and low surface capacitance of titanium oxide nanotube array electrode materials, thereby providing a simple and controllable method for preparing defect-metal-doped titanium oxide nanotube array supercapacitor electrode materials with high charge transfer efficiency, high rate performance and high surface capacitance characteristics.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a defective metal-doped titanium oxide nanotube array supercapacitor electrode material, the specific steps are as follows:

[0009] (1) polishing and drying Ti-Nb alloy as an anode, and obtaining an amorphous Nb-doped titanium oxide nanotube array electrode material by an anodic oxidation method;

[0010] (2) subjecting the electrode material obtained in step (1) to high temperature heat treatment to obtain a crystalline phase Nb-doped titanium oxide nanotube array electrode material;

[0011] (3) The electrode material obtained in step (2) is used as a cathode, and Ti is obtained after electrochemical reduction. 3+ / Oxygen vacancies and Nb co-doped titanium oxide nanotube array electrode material, that is, defect-metal-doped titanium oxide nanotube array supercapacitor electrode material.

[0012] The present invention uses a Ti-Nb alloy sheet as a substrate material, adopts an anodic oxidation method to in-situ grow a nanotube array on the alloy substrate, obtains a crystallized Ti-Nb-O nanotube array after high-temperature heat treatment in a muffle furnace, and then adopts a simple and fast electrochemical reduction method to introduce an appropriate amount of Ti on the surface of the electrode material. 3+ / oxygen vacancies, that is, a defect-type metal-doped titanium oxide nanotube array supercapacitor electrode material with high specific surface area, high charge transfer efficiency and high electrochemical performance is prepared. This method has the remarkable characteristics of low production cost, short preparation time, convenient and quick operation, etc.

[0013] Furthermore, in step (1), the Ti-Nb alloy is prepared by low vacuum arc casting, and the Nb content is wt. 5% to 15%.

[0014] Furthermore, the sandpaper used for polishing the titanium alloy in step (1) is 240#, 400#, 800#, 1000# and 1500# waterproof Al 2 O 3 sandpaper.

[0015] Furthermore, in step (1), the anodic oxidation method is specifically: a two-electrode anodic oxidation method is adopted, Ti-Nb alloy is used as an anode, graphite is used as a cathode, and the electrolyte is 0.4wt.% NH 4 F and 2 vol.%H 2 O in ethylene glycol solution, the distance between the two electrodes is 3.5 cm, the anodic oxidation constant current voltage is 35-45 V, and the anodic oxidation time is 0.5-2 h.

[0016] Furthermore, in step (2), the high temperature heat treatment is specifically as follows: the electrode material obtained in step (1) is heated to 300-500° C. in a muffle furnace, kept at this temperature for 2 hours, and then cooled to room temperature in the furnace.

[0017] Further, in step (3), the electrochemical reduction method is specifically: using a two-electrode reduction method, the heat-treated material is used as a cathode, and graphite is used as an anode, and immersed in 0.4-0.6M Na 2 SO 4 In the electrolyte, the reduction voltage is 3-5V and the reduction time is 3-5min.

[0018] Furthermore, the Ti-Nb alloy is a Ti-Nb alloy prepared by vacuum arc melting, and the Nb content is 5-15wt.%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] In the present invention, Nb bulk doping can inhibit the formation of rutile phase during high-temperature heat treatment, so that it forms anatase phase with smaller grains and higher charge transfer efficiency, and at the same time can generate local electronic energy levels in the band gap to improve the charge transfer efficiency; Nb doping can form a nanotube array with smaller pore size and longer tube length, significantly increasing the specific surface area and providing more active sites for charge adsorption. At the same time, this invention adopts a low-cost and easy-to-operate electrochemical reduction method to introduce Ti on the surface of the electrode material. 3+ / oxygen vacancies, producing non-stoichiometric effects, greatly exerting the 3+ The synergistic doping advantages of oxygen vacancies make the electrode material have higher electrochemical properties. The method of the present invention also has the characteristics of non-toxic and harmless preparation process, simple operation, high repeatability, etc., and has broad application prospects and market potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are the CV and GCD diagrams of the R-Ti-5Nb-O electrode material prepared in Example 1 / 2 / 3.

[0022] Figure 2 These are the CV and GCD diagrams of the R-Ti-5Nb-O electrode material prepared in Example 1 / 4 / 5.

[0023] Figure 3 These are the CV and GCD diagrams of the electrode materials prepared in Example 1 / 6 / 7.

[0024] Figure 4 These are the CV and GCD diagrams of the electrode materials prepared in Example 1 and Comparative Examples 1 / 2 / 3.

[0025] Figure 5 It is the EIS graph of the electrode materials prepared in Example 1 and Comparative Examples 1 / 2 / 3.

[0026] Figure 6 It is the XPS full spectrum and O1s high-resolution spectrum of the electrode materials prepared in Example 1 and Comparative Example 2 / 3 (Example 1). DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] Example 1

[0029] A method for preparing a defective metal-doped titanium oxide nanotube array supercapacitor electrode material, comprising the following steps:

[0030] (1) A Ti-5wt.% Nb alloy with a size of 10 mm × 20 mm × 1 mm was prepared using 240#, 400#, 800#, 1000# and 1500# waterproof Al 2 O3 The surface was polished with sandpaper to remove the original oxide film; after polishing, it was immersed in acetone, anhydrous ethanol and deionized water for 10 minutes in sequence, and then taken out and blown dry with compressed air.

[0031] (2) Ti-Nb alloy was connected to the anode and graphite was connected to the cathode, and the electrolyte was immersed in 0.4wt.% NH 4 F and 2 vol.% H 2 O in ethylene glycol solution, the distance between the two electrodes is 3.5 cm, the anodic oxidation DC voltage is 40 V, the anodic oxidation time is 1 h, and after removal, it is rinsed with deionized water and blown dry with compressed air.

[0032] (3) The amorphous nanotube array is placed in a muffle furnace, heated to 400°C, kept at this temperature for 2 hours, and then cooled to room temperature.

[0033] (4) The electrode material obtained in step (3) is electrochemically reduced, the electrode material is connected to the cathode, the graphite is connected to the anode, and immersed in 0.5M Na 2 SO 4 The electrolyte is neutral, the reduction voltage is 3V, and the reduction time is 4min. After reduction, rinse with deionized water and blow dry with compressed air.

[0034] Obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-5Nb-O electrode material at 0.005 mA cm -2 At a current density of , the surface capacitance is 9.66 mF cm -2 .

[0035] Example 2

[0036] The same anodizing process as in Example 1 was used, and then the temperature was raised to 350°C in a muffle furnace and kept at this temperature for 2 hours. The crystallized electrode material was connected to the cathode and immersed in 0.5M Na 2 SO 4 In the electrolyte, under 3V constant current voltage, reduction was carried out for 4 minutes to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-5Nb-O electrode material at 0.005 mA cm -2 At a current density of 1.34 W, the surface capacitance is 7.26 mF cm -2 .

[0037] Example 3

[0038] The same anodizing process as in Example 1 was used, and then the temperature was raised to 450°C in a muffle furnace and kept at this temperature for 2 hours. The crystallized electrode material was connected to the cathode and immersed in 0.5M Na 2 SO4 In the electrolyte, under 3V constant current voltage, reduction was carried out for 4 minutes to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-5Nb-O electrode material at 0.005 mA cm -2 At a current density of , the surface capacitance is 6.94mF cm -2 .

[0039] Example 4

[0040] The same anodization and heat treatment process as in Example 1 was used, and then the electrode material was connected to the cathode and immersed in 0.5M Na 2 SO 4 In the electrolyte, under a constant current voltage of 3V, reduction was carried out for 3 minutes to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-5Nb-O electrode material at 0.005 mA cm -2 At a current density of 1.34 W, the surface capacitance is 7.23 mF cm -2 .

[0041] Example 5

[0042] The same anodization and heat treatment process as in Example 1 was used, and then the electrode material was connected to the cathode and immersed in 0.5M Na 2 SO 4 In the electrolyte, under a constant current voltage of 3V, reduction was carried out for 5 minutes to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-5Nb-O electrode material at 0.005 mA cm -2 At a current density of , the surface capacitance is 6.71mF cm -2 .

[0043] Example 6

[0044] Ti-10wt.%Nb alloy was used as the anode, and the same anodizing process, heat treatment process and electrochemical reduction process as in Example 1 were used to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-10Nb-O electrode material at 0.005 mA cm -2 At a current density of 1.38 mF cm, the surface capacitance is 13.48 mF cm -2 .

[0045] Example 7

[0046] Ti-15wt.%Nb alloy was used as the anode, and the same anodizing process, heat treatment process and electrochemical reduction process as in Example 1 were used to obtain Nb and Ti 3+ / oxygen vacancy co-doped R-Ti-15Nb-O electrode material at 0.005 mA cm-2 At a current density of 1.34 W, the surface capacitance is 14.57 mF cm -2 .

[0047] Comparative Example 1

[0048] The same anodic oxidation and heat treatment process as in Example 1 was used to prepare a raw titanium oxide nanotube array on the surface of a pure titanium sheet, and then the same electrochemical reduction process as in Example 1 was used to obtain Ti 3+ / oxygen vacancy doped R-Ti-O electrode material at 0.005 mA cm -2 At a current density of 1.34 W, the surface capacitance is 3.25 mF cm -2 .

[0049] Comparative Example 2

[0050] The same anodization and heat treatment process as in Example 1 was used to obtain a crystallized Ti-5Nb-O electrode material. -2 At a current density of 1.34 W, the surface capacitance is 0.033 mF cm -2 .

[0051] Comparative Example 3

[0052] The same anodizing and heat treatment process as in Example 1 was used to prepare a pristine titanium oxide nanotube array on the surface of a pure titanium sheet, i.e., a crystallized Ti-O electrode material was obtained. -2 At a current density of 1.34 W, the surface capacitance is 0.021 mF cm -2 .

[0053] Table 1 Electrochemical properties of electrode materials obtained in Examples and Comparative Examples

[0054]

[0055] In summary, the method for preparing defective metal-doped titanium oxide nanotube array supercapacitor electrode material provided by the present invention successfully prepares metal and Ti 3+ / oxygen vacancy co-doped titanium oxide nanotube arrays, which fully utilizes the metal and Ti 3+ The synergistic advantages of titanium / oxygen vacancies greatly improve the electrochemical properties of titanium-based nanomaterials.

[0056] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material, characterized in that: The following steps are involved: (1) Pre-treating the Ti-Nb alloy, using the Ti-Nb alloy as an anode, and obtaining an amorphous Nb-doped titanium oxide nanotube array electrode material by an anodic oxidation method; (2) subjecting the electrode material obtained in step (1) to high temperature heat treatment to obtain a crystalline Nb-doped titanium oxide nanotube array electrode material; (3) Using the electrode material obtained in step (2) as the cathode, Ti is obtained by electrochemical reduction. 3+ / oxygen vacancies and Nb co-doped titanium oxide nanotube array electrode material, that is, defect-metal-doped titanium oxide nanotube array supercapacitor electrode material; Nb bulk doping inhibits the formation of rutile phase during high-temperature heat treatment, resulting in the formation of anatase phase with smaller grains and higher charge transfer efficiency. At the same time, local electronic energy levels are generated in the band gap to improve the charge transfer efficiency. Nb doping can form nanotube arrays with smaller pores and longer tubes, significantly increasing the specific surface area and providing more active sites for charge adsorption. Ti is introduced on the surface of the electrode material by electrochemical reduction. 3+ / oxygen vacancies, producing non-stoichiometric effects, exerting the effects of metal and Ti 3+ The synergistic doping advantages of ions / oxygen vacancies give the electrode materials higher electrochemical properties.

2. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 1, characterized in that: In step (1), the anodic oxidation method is specifically as follows: Ti-Nb alloy is used as an anode and graphite is used as a cathode, which are immersed in an electrolyte and a voltage is applied to the anode for a certain period of time.

3. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 2, characterized in that: The electrolyte is an ethylene glycol solution of 0.4 wt.% NH4F and 2 vol.% H2O.

4. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 2, characterized in that: The distance between the two electrodes is 3.5 cm, the anodic oxidation DC voltage is 35-45 V, and the oxidation time is 0.5-2 h.

5. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 1, characterized in that: In step (2), the high temperature heat treatment is specifically as follows: placing the amorphous electrode material obtained after anodization in a muffle furnace, heating it to 300-500 °C, keeping it at that temperature for 1-3 h, and then cooling it to room temperature in the furnace.

6. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 1, characterized in that: In step (3), the electrochemical reduction method specifically comprises: using the electrode material obtained in step (2) as a cathode and graphite as an anode to perform electrochemical reduction in a solution.

7. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 6, characterized in that: In step (3), electrochemical reduction is carried out in a 0.4-0.6M Na2SO4 aqueous solution.

8. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 6, characterized in that: In step (3), the reduction voltage is 3-5 V and the reduction time is 3-5 min.

9. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to any one of claims 1 to 8, characterized in that: The Ti-Nb alloy is a Ti-Nb alloy prepared by vacuum arc melting, and the Nb content is 5-15 wt.%.

10. The method for preparing a defect-metal-doped titanium oxide nanotube array supercapacitor electrode material according to claim 9, characterized in that: Defective-metal-doped titanium oxide nanotube array supercapacitor electrodes are Nb and Ti 3+ / oxygen vacancy co-doped titanium oxide nanotube arrays.

Citation Information

Patent Citations

  • Reduction-state Si-doped titanium dioxide nanotube photo-anode and preparation method thereof

    CN112430827A

  • Preparation method of mixed crystal phase niobium-doped titanium dioxide nanotube array photo-anode

    CN113355694A